2020
DOI: 10.1002/app.50270
|View full text |Cite
|
Sign up to set email alerts
|

A modified creep model of polylactic acid (PLA‐max) materials with different printing angles processed by fused filament fabrication

Abstract: The creep behavior caused by the viscous mechanical effect of biodegradable polylactic acid (PLA‐max) material is of great significance to its application. To better understand the creep properties of PLA‐max materials processed by fused filament fabrication, the effects of printing parameters including printing angle and layer thickness on them are studied theoretically and experimentally. The experimental results show that within the range of loading stress and loading time, the creep deformation of the PLA‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
1
7
0
1
Order By: Relevance
“…On the other hand, because VMT‐PLA‐ICs cannot be dispersed well, they will agglomerate in PLA. VMT‐PLA‐ICs particles hindered the movement of PLA molecular chains; it cannot give PLA shape memory function well 52 . This was consistent with the mechanical properties results of PLA/VMT‐PLA‐ICs nanocomposites.…”
Section: Resultssupporting
confidence: 84%
“…On the other hand, because VMT‐PLA‐ICs cannot be dispersed well, they will agglomerate in PLA. VMT‐PLA‐ICs particles hindered the movement of PLA molecular chains; it cannot give PLA shape memory function well 52 . This was consistent with the mechanical properties results of PLA/VMT‐PLA‐ICs nanocomposites.…”
Section: Resultssupporting
confidence: 84%
“…Wang et al [ 12 ] explored the mechanical properties of the FDM process under different process parameters, including the printing angle, layer thickness, the fill rate and the nozzle temperature of PLA by using uni-axial tensile tests and a dynamic mechanic analysis. Yao et al and Ye et al [ 13 , 14 ] established a theoretical model for predicting the failure strength, separation angle and creep deformation of PLA material under a tensile load. The predicted capacity was affirmed by the experimental data and the results indicated that an increased printing angle and a decreased layer thickness can improve the tensile strength of PLA significantly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These distortions occur due to the actual displacement of the molecules over each other, which causes permanent deformation [ 27 , 28 ]. In [ 29 ], the creep behavior of biodegradable PLA was analyzed, considering the effects of layer thickness and printing angle. Creep response was also modeled by using Burger model for predictive purposes.…”
Section: Introductionmentioning
confidence: 99%